Analysis of Palm Sugar Business Development Strategy in Increasing Income in Bahorok District, Langkat Regency from the Perspective of Maqashid Syariah - Baihaqi, M. Eza; Imsar, Imsar; Harahap, Muhammad Ikhsan (Journal of Economics and Social Sciences (JESS), 2025)
The primary objective of this study is to examine the income earned by the palm sugar business community group in Bahorok District, Langkat Regency, through the lens of Maqashid Sharia. This research adopts a qualitative approach, with data collected through direct interviews with palm sugar entrepreneurs in the region. A total of ten respondents were selected from two villages in Bahorok District. Data collection methods included observation, interviews, and documentation. The findings reveal that the palm sugar household industry in Bahorok District significantly contributes to improving the community’s economic conditions, as reflected in the income generated from sales. The production of palm sugar from processed palm sap plays a crucial role in increasing household income. Within the framework of Maqashid Sharia, production activities must prioritize the realization of benefits (maslahah) and the prevention of harm (mafsadah). The concept encompasses five key elements: the preservation of religion, life, lineage, intellect, and wealth. Based on the analysis, the most prominent aspect observed among palm sugar artisans in Bahorok District is the preservation of wealth (Hifdz al-Mal). This is evident from the way their income supports family health, education, food, and clothing needs, thereby ensuring their economic welfare. Moreover, the safeguarding of wealth is consistently aligned with income sources obtained through lawful means, in accordance with Islamic law, which is an absolute principle to be upheld.